Object Detection with Discriminatively Trained Part-Based Models. - Forsyth, David (Computer (00189162), 2014)
This installment of Computer's series highlighting the work published in IEEE Computer Society journals comes from IEEE Transactions on Pattern Analysis and Machine Intelligence.